PERAN GURU DALAM MENANGANI RASA MALU ANAK USIA DINI MELALUI PERMAINAN LOMPAT TALI (Studi Kasus Pada Anak Kelompok B di TK Muslimat NU 46) - Ruly Afidatu Nurhasanah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
One of the early childhood social-emotional problems that often occur in school is shyness. Shyness tends to cause children to become less skilled, less confident, less able to interact socially and unable to adjust to their environment. So it takes the role of teachers in overcoming the shy nature of children at school. The purpose of writing the article is to illustrate the role of teachers in dealing with children's shyness through jumping rope games. This research uses a qualitative approach with a type of case study research (case study) and is descriptive. Data collection techniques in this study are interviews, observation and documentation. The results of this study showed that one shy child in group B saw an increase in his social-emotional development, the presence of painstaking teachers to overcome shy children through jumping rope games fostered self-confidence in children.